2016
DOI: 10.1124/jpet.116.232819
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Skin Inflammation with Benzoxaborole Phosphodiesterase Inhibitors: Selectivity, Cellular Activity, and Effect on Cytokines Associated with Skin Inflammation and Skin Architecture Changes

Abstract: Psoriasis and atopic dermatitis are skin diseases affecting millions of patients. Here, we characterize benzoxaborole phosphodiesterase (PDE)-4 inhibitors, a new topical class that has demonstrated therapeutic benefit for psoriasis and atopic dermatitis in phase 2 or phase 3 studies.are potent PDE4 inhibitors with similar affinity for PDE4 isoforms and equivalent inhibition on the catalytic domain and the full-length enzyme. These benzoxaboroles are less active on other PDE isozymes. Compd4 binds to the cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 76 publications
0
40
0
Order By: Relevance
“…84 PDE4 antagonism inhibits production of many inflammatory mediators, including T H 1related (IFN-g), T H 2-related (IL-5), and T H 17-related (IL-8) products in model systems. 15,48,51,[81][82][83][85][86][87][88] In patients with psoriasis treated with the systemic PDE4 inhibitor apremilast, the greatest molecular inhibition is observed for T H 17/T H 22 pathway genes (IL17, IL22, and IL23). 42,51,80,[89][90][91][92][93] T H 17/T H 22centered suppression was also observed in AD lesions in patients treated with 40 mg of apremilast.…”
Section: Discussionmentioning
confidence: 99%
“…84 PDE4 antagonism inhibits production of many inflammatory mediators, including T H 1related (IFN-g), T H 2-related (IL-5), and T H 17-related (IL-8) products in model systems. 15,48,51,[81][82][83][85][86][87][88] In patients with psoriasis treated with the systemic PDE4 inhibitor apremilast, the greatest molecular inhibition is observed for T H 17/T H 22 pathway genes (IL17, IL22, and IL23). 42,51,80,[89][90][91][92][93] T H 17/T H 22centered suppression was also observed in AD lesions in patients treated with 40 mg of apremilast.…”
Section: Discussionmentioning
confidence: 99%
“…The catalytic domain of PDE4 has been extensively studied and x-ray crystal structures reveal details of the active site that enabled the design of family-specific inhibitors [10] [11].…”
Section: The Pde4 Isoenzyme Familymentioning
confidence: 99%
“…• X-ray crystal structures of the catalytic domain of PDE4 isozymes make the design of small molecule inhibitors feasible [11] [32]. • Experimental and clinical evidence have demonstrated that increases in intracellular levels of cAMP will lead to inhibition of formation of multiple mediators of inflammation in several cell types known to be responsible for these inflammatory skin conditions [33].…”
Section: Role Of Pde4 Inhibitor Therapy In the Management Of Ad And Pmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a small molecule phosphodiesterase-4 inhibitor (apremilast) works by preventing cAMP activation in immune cells, thereby limiting pro-inflammatory cytokine production [42][43][44][45]. It should be noted, however, that initial clinical trials were discontinued due to unexpected side effects such as diarrhoea, headache and nausea, although careful re-examination of dosing regiments and/or new molecular modifications may still be possible.…”
Section: Inflammatory Cytokines In Psoriasis (And Psoriatic-type Arthmentioning
confidence: 99%